FUNGSI DEDAKTIS LOLOH DON PIDUH TERHADAP PENINGKATAN DAYA INGAT - Ni Made Sinarsi (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2021)
Memory is very important for every individual. The memory process plays a very important role in daily activities, including the learning process. The part of the brain that plays a role in memory processing is the hippocampus. The incidence of memory loss as an early sign of Alzheimer's disease dementia worldwide is increasing rapidly and is currently estimated to be approaching 46.8 or 50 million people diagnosed with dementia in the world, 20.9 million in Asia Pacific. Various ways are used to reduce the process of memory loss or efforts to improve memory. Therefore, other alternatives are sought to improve short-term memory, one of which is by using herbal plants. Don piduh is an example of an herbal plant that can be used to improve short-term memory skills.